State of speech parameters in subjects with chronic obstructive pulmonary disease (COPD): A case-series report - Gay, Joaquín (2018)
Objective: To characterize the speech parameters in patients with chronic obstructive pulmonary disease (COPD). Materials and methods: A prospective case-series study. All patients underwent an evaluation of the following speech parameters: maximum phonation time, oral-motor control, articulation, reading, verbal diadochokinesia, and automatic speech. The mean, median and standard deviation of these parameters were determined using SPSS software version 23. Results: Twenty (20) subjects (7 males and 13 females) whose average age was 64.4 ± 9.1 years entered the study. The speech parameters showed a reduction in the maximum phonation time (MPT) in /s/ 6.58 ± 6.76, /a/ 7.29 ±5.08, /i/ 8.24 ± 5.72. The same happened in the repetition tasks: /pa/ 12.60 ± 3.36, /ta/ 13.40 ± 3.4, /ka/ 12 ±4.11, and the number of words per minute accounted for 109 ± 26.25. Conclusions: The study results suggest that patients with COPD show an impairment in speech parameters. This represents an opportunity to increase research on this topic and thus consider the speech in the comprehensive clinical care.